2001
DOI: 10.1046/j.1440-1622.2001.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Documented prevalence of HIV and Hepatitis C infection in patientswith penetrating trauma

Abstract: There was a high prevalence of risk factors for HIV and HCV in patients with major penetrating wounds at St Vincent's Hospital. The prevalence of documented HIV and HCV infection was subsequently greater than that expected in the general population, highlighting the risks to health-care workers managing these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In one study, risk factors for HIV infection were recorded in 21%, and a high prevalence of risk factors for HIV was found in patients with major penetrating wounds (Chambers & Lord, 2001). In a study in the USA, intravenous drug abuse was found to be the single significant predictor for HIV infection among trauma patients (Sloan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, risk factors for HIV infection were recorded in 21%, and a high prevalence of risk factors for HIV was found in patients with major penetrating wounds (Chambers & Lord, 2001). In a study in the USA, intravenous drug abuse was found to be the single significant predictor for HIV infection among trauma patients (Sloan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Trauma health care workers will encounter patients infected 1 with HIV in geographic areas where prevalence is high or in areas where intravenous drug abuse use, high-risk sexual behaviors and penetrating trauma are more common (Kelen et al, 1989). Studies of patients with penetrating trauma in the USA have shown a higher prevalence of HIV infection than the general population (Chambers & Lord, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies have identified relatively higher rates of HIV and hepatitis C in trauma patients than the general population. 3,5,7 One German study conducted HIV studies on patients with open wounds in the trauma emergency room of a university hospital and found six HIV infections in 220 patients tested, corresponding to a prevalence of 2.7%. 5 Chambers and Lord 3 documented a prevalence of HIV (1.3%) and hepatitis C (5.4%) in penetrating injuries in one hospital in Sydney, Australia.…”
Section: Discussionmentioning
confidence: 99%